Cognitive poetics and biocultural (con)figurations of life, cognition and language. Towards a theory of socially integrated science - Guerra, Juani (Pensamiento. Revista de Investigación e Información Filosófica, 2013)
Based on the biocultural dynamics of Greek poiesis and autopoiesis as evolutionary processes of meaning evaluative (con)figuration, Cognitive Poetics proposes key methodological adjustments, mainly at the philological, ontological and cultural levels. The aim is to improve our understanding of cognitive and conceptual activity and the social foundations of individual language. From its new status as a fundamental metacognitive theory, it searches for a theory of socially integrated sciences from a new alliance as that discerned in current Cognitive Sciences: from Linguistics or Psychology, through Anthropology, Neurophilosophy or Literary Studies, to Neurobiology or Artificial Life Sciences. From a realist turn to a view of cognition as (social) action, it provides new unforeseen accounts of the complex dynamics of human understanding processes studying and analyzing all form of texts as active data